Inverse problems for the dynamic characterization of materials (2014)
The problem of mechanical characterization of materials is an active research field, especially when it comes to identifying the constant parameters associated with a constitutive equation. The challenge in determining the fittest set of material parameters that describe the mechanical behavior of the material is the selection of an adequate combination of an experimental technique with an optimization procedure. This challenge is accentuated in the characterization of materials at high strain rates due to the absence of standard test methods, the use of more complicated experimental techniques and the need for sophisticated strength models that describe the dependency of the material to the strain rate. In this work, a computational technique to characterize materials at high strain rates is developed. The proposed characterization technique is based on the statement and solution of inverse problems of high strain rate experimental tests. Finite element analysis, genetic algorithm optimization and image processing by central line moments are used as operating tools to integrate a computational characterization procedure. Case studies using experimental techniques such as the Taylor test, the split Hopkinson pressure bar test and the drop test were implemented to demonstrate the performance of the proposed characterization technique